2014
DOI: 10.1111/fcsr.12062
|View full text |Cite
|
Sign up to set email alerts
|

Socially Responsible Apparel Labels: Effects on Fashionable Shoppers

Abstract: Although socially responsible (SR) labels can facilitate consumers' SR purchasing choices, research addressing the effectiveness of SR labels for apparel products is limited. The purpose of this study was to investigate the consumer segment that practices SR label reading behavior and plans to purchase SR apparel. An online survey was conducted with a random sample of U.S. consumers (N = 718). The researchers used cluster analysis to segment participants based on the participants' fashion orientation and shopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
1
21
0
2
Order By: Relevance
“…Previous studies (Dickson 2001;Gam et al 2014) indicate that consumers who are more likely to purchase sustainability-labelled products exhibit different characteristics than those who are not. Findings showed that a consumer's previous usage or purchasing experiences are the strongest indicator of an actual purchase.…”
Section: Research Objectives and Hypotheses Developmentmentioning
confidence: 99%
“…Previous studies (Dickson 2001;Gam et al 2014) indicate that consumers who are more likely to purchase sustainability-labelled products exhibit different characteristics than those who are not. Findings showed that a consumer's previous usage or purchasing experiences are the strongest indicator of an actual purchase.…”
Section: Research Objectives and Hypotheses Developmentmentioning
confidence: 99%
“…To safeguard against this, the preamble was also used to define ERC for respondents, and to do so using descriptors adapted from existing scale items (i.e. Chan & Wong, 2012;Gam et al, 2014). This resulted in the following preamble:…”
Section: Attitude Contextmentioning
confidence: 99%
“…Responses for all seven constructs employed in this study were measured on a 7-point scale (1=strongly disagree, 7= strongly agree). The scales used to measure the four independent variables -environmentally responsible (Gam et al, 2014;Kim & Damhorst, 1998), employee welfare (Auger et al, 2003), slow fashion (Kim et al, 2013) and animal welfare (Auger et al, 2003) -were adapted from existing scales, as were the variables overall attitude (Shen et al, 2012) and purchase intention (Watchravesringkan et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…To avoid this very risk, previous studies employing the term have sometimes provided preambles in order to clarify its meaning to respondents. For example, Gam et al (2014) informed their consumer participants that the term 'socially responsible' refers to sustainable practices such as environmental friendliness and fair labour conditions. However the use of such preambles for the purpose of this study would create bias by effectively defining the construct for respondents.…”
Section: Inconsistent Use Of Terminologymentioning
confidence: 99%
See 1 more Smart Citation